Telling the truth to young children: Ethical reasons for information disclosure in paediatrics. (9th September 2018) - Hudson, Nicholas; Spriggs, Merle; Gillam, Lynn
Abstract: When parents ask doctors not to disclose certain information to a child, doctors are challenged to articulate ethical reasons for giving information to children. This paper maps out the professional and legal landscape in which information‐giving to children is taking place and identifies the key ethical arguments that have been made for disclosure of information to the child patient. We focus on pre‐adolescent children, who have not reached a developmental stage that would see them regarded as 'mature minors'. While doctors can be relatively certain that professional and legal requirements will endorse their disclosure of information to the 'mature minor', guidelines are not clear on information‐giving to pre‐adolescents (immature minors). We identify six ethical reasons for telling the truth to younger children. It is noteworthy that there are good reasons to tell the truth to children, which are independent of any question of the child's capacity to be involved in decision‐making.